Addressing Gender-Based Violence (GBV) in rural Nepal with One-Stop Crisis Management (OCMC) approach - Dangal, Binod; Khadka, Man Bahadur; Moktan, Sunil; Khadka, Sunil; Ghimire, Rajesh; Dahal, Rashmi; Tamang, Dhanlal Dong; Kayastha, Sanjita; Jirel, Sunita; Bajagain, Gopal (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Gender-Based Violence (GBV) is a global challenge and is affecting 1 in 3 women in their lifetime. GBV mainly includes physical and domestic violence, rape, mental torture, child marriage, and human trafficking. There are very few specific programs to address GBV in Nepal and the One-Stop Crisis Management (OCMC) approach started by the Nepal government since 2011, has promising support in addressing genderbased issues.Method: Study was conducted at Charikot Hospital, Dolakha. Retrospectively collected data from Electronic Health Record (EHR) of Bahmini from 2016 September to 2021 August, were used and were verified using the OCMC register. The quantitative data were analyzed using descriptive statistics and presented in relevant tables and frequencies. The nature of the study was exploratory as a researcher had tried to explore the effectiveness of the program and its challenges.Result: Out of 750 cases over 5 years, 695(92.7%) were female, 272(36.2%) were sexual assault cases followed by 259 (34.5%) of physical assault, 73.6% of the victims were among 15-49 years of age and most commonly affected among Janajati (40%) and Brahmin/Chhetri (39.5%). Almost 15% of the total victims had some form of disability. Twenty-one women had difficulties finding safe homes and 7 women committed suicide and died.Conclusion: Initiation of OCMC services at district level hospitals has formed the foundation to support GBV victims. A specific mental health approach is needed to prevent deaths due to suicide. Government should ensure infrastructure for safe homes and give priority to medicolegal cases. Awareness campaigns are necessary to report more cases of GBV.